The Araceae of Indomalaya II: Piptospatha N.E.Br. - Boyce, P.C; Wong Sin, Yeng (Malaysian Nature Society, 2012)
A review of the genus Piptospatha N.E.Br. is presented with new generic boundaries implemented since the last full revision. 10 species are recognized, two of them (P. marginata (Engl.) N.E.Br. & Piptospatha repens H.Okada & Tsukaya) only recently recognized as distinct species. A key to species is given and species are illustrated, the majority from living plants.